Design of SBAR Communication Application Based on National Hospital Accreditation Standards and Imogene King's Theory in a Digital-Based Handover at Advent Bandung Hospital - Viere Allanled Siauta; Iin Inayah; Lilis Rohayani (Utan Kayu Publishing, 2023)
Nurses face challenges in developing skills and adaptability in line with technological advancements. Their primary focus is patient safety, emphasizing effective communication, particularly in the patient handover process. Communication errors can have serious consequences, impacting patient safety. The implementation of digital technology, such as SBAR applications, is considered a positive step to enhance collaboration and patient safety, reflecting a shift in communication paradigms in the era of the 4.0 industrial revolution. This research aims to develop a Digital SBAR Communication Application for Patient Handover in Hospital Nursing Services. The research method used is qualitative with a research and development approach. The study is conducted at Advent Hospital Bandung, West Java Province, involving research subjects from various stakeholders, including experts in Information System, Nursing Management, Hospital Director, Head of Nursing Department, Nursing Committee, and Head of Hospital Ward. Data analysis is carried out through stages of research and information collection, planning, and developing the preliminary form of the product, focusing on information gathering, research planning, and SBAR application design development. The researcher takes a series of steps, including interviews through FGD with participants. The initial application design is revised after receiving input, and development is carried out by IT professionals. The application is tested by experts according to their competencies, with expert feedback used for improvement. After testing and refinement stages, the application is introduced to participants. The research results indicate that the prototype product successfully addresses issues related to data and information in the patient handover process at Advent Hospital Bandung. Expert testing by professionals in the field validates the application design developed by the researcher to address hospital issues. The product receives positive feedback from participants. Abstrak: Perawat menghadapi tantangan dalam mengembangkan keterampilan dan adaptabilitas sesuai dengan kemajuan teknologi. Fokus utama mereka adalah keselamatan pasien, dengan penekanan pada komunikasi efektif, terutama dalam proses serah terima pasien. Kesalahan dalam komunikasi dapat memiliki konsekuensi serius, termasuk dampak pada keselamatan pasien. Penerapan teknologi digital, seperti aplikasi SBAR, dianggap sebagai langkah positif untuk meningkatkan kolaborasi dan keselamatan pasien, mencerminkan perubahan paradigma komunikasi di era revolusi industri 4.0. Penelitian ini bertujuan untuk melakukan pengembangan Aplikasi Komunikasi SBAR Berbasis Digital dalam Melakukan Handover di Pelayanan Keperawatan Rumah Sakit. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan penelitian dan pengembangan (Research and Development). Lokasi penelitian dilakukan di Rumah Sakit Advent Bandung, Provinsi Jawa Barat, melibatkan subjek penelitian dari berbagai pihak, termasuk ahli media Sistem Informasi, pakar Manajemen Keperawatan, Direktur Rumah Sakit, Kepala Bidang Keperawatan, Komite Keperawatan, dan Kepala Ruangan Rumah Sakit. Analisis data dilakukan melalui tahapan research and information collection, planning, dan develop preliminary form of product, dengan fokus pada pengumpulan informasi, perencanaan penelitian, dan pengembangan desain aplikasi SBAR. Peneliti melakukan serangkaian langkah, termasuk wawancara melalui FGD dengan partisipan. Desain awal aplikasi direvisi setelah mendapatkan masukan, dan pengembangan dilakukan oleh tenaga IT. Aplikasi diuji oleh pakar sesuai kompetensi, dengan masukan pakar digunakan untuk perbaikan. Setelah tahap pengujian dan perbaikan, aplikasi tersebut disosialisasikan kepada partisipan. Hasil penelitian menunjukkan bahwa prototipe produk berhasil mengatasi permasalahan terkait data dan informasi dalam proses handover pasien di Rumah Sakit Advent Bandung. Uji pakar oleh para ahli dalam bidangnya memvalidasi rancangan aplikasi yang dikembangkan oleh peneliti untuk menjawab permasalahan di rumah sakit tersebut. Produk tersebut mendapatkan tanggapan positif dari partisipan.